The riverside way of life as a spatial attribute for the design practice of Amazonian housing - Guimarães, Danielle Costa; Perdigão, Ana Klaudia de Almeida Viana (Revista Nacional de Gerenciamento de Cidades, 2024)
The production of social housing in the Amazon does not differ from that found in other regions of Brazil, as the lack of adequacy in the projects is a historical and ongoing issue. This essay aims to raise questions about the inadequacy of housing projects for Amazonian cities. Reference is made in this investigation to the Amazonian imaginary, the origins of local ways of living, and the results of research projects already carried out by local researchers. Non-participant observations were also conducted in urban housing areas in the city of Belém. In this sense, it was observed that there are strong indications that the closer to the original way of life of the region's inhabitants, the riverside dwellers, the less likely transformations in housing promoted by the government are to occur. In the study reports, a typological language of riverside dwelling was identified in the modifications made to these state-owned housing units, serving as a mechanism of adaptation in housing. It has been noted that there is a mismatch between the user's needs and state action/production, and understanding the symbolic communications established between people and the built space may likely be beneficial in reducing the existing imbalance between user expectations and project quality in state offerings. Therefore, rethinking the ways of designing and producing architectural living spaces from the local user's perspective is a secure path for the sustainability of the project, encompassing the development of people and space vitality.